Development of a model for estimating the sensitivity of Canadian peatlands to climate warning - Kettles, Inez; Tarnocai, Charles (Géographie physique et Quaternaire, 1999)
Abstract Under current scenarios of increasing greenhouse gases, the expected increases in global temperatures have the potential to affect, in many areas, the peat- lands that now cover 14 % of the soil area of Canada. A model for estimating peatland sensitivity to climate warming was developed using published information on the current state of climate, vegetation, and permafrost together with the changes expected with a doubling of CO 2 . Calculations based on this sensitivity model and data for the areal extent and carbon content of organic soils in Canada, show that approximately 60 % of the area of Canadian peatlands is expected to be severely to extremely severely affected by climate warming. These peatlands, which are deemed most sensitive to climate warming, also contain 53 % of the 154 Gt of carbon found in organic soils.